(3, -2)
Step-by-step explanation:
y = -2x + 4
-x + 3y = -9
-x + 3 (-2x + 4) = -9
-x + -6x + 12 = -9
-7x = - 9 – 12
-7x = - 21
X = 3
We substitute x with 3 to evaluate y;
-3 + 3y = -9
3y = -6
y = -2
Elimination Method;
y = -2x + 4
-x + 3y = -9
We arrange the equations for substitution;
2x + y = 4
-x + 3y = -9
We multiply the first equation with 3 so we can substract one variable to zero;
3 (2x + y = 4)
= 6x + 3y = 12
Then we subtract the two;
6x + 3y = 12
-x + 3y = -9
7x = 21
x = 3
We evaluate y by substitution x with 3 in one of the equation;
-x + 3y = -9
-3 + 3y = -9
3y = -6
y = -2
The final answer expressed as a coordinate point is;
(3, -2)
Answer:
its b :) then can i help you
Answer:
∠X in the pre-image will be equal to ∠L in the main image
Step-by-step explanation:
△LMN is the result of a reflection of △XYZ which means △LMN is the mirror image △XYZ
hence, the left of △XYZ will be equivalent to the right of △LMN and the right of △XYZ will be equivalent to the left of △LMN
Hence, ∠X in the pre-image will be equal to ∠L in the main image
Answer:
5 stars? Answer down below
Step-by-step explanation:
a+b=350 => a=350 - b
3a + 5b = 1450
3(350-b)+b=1450
1050-3b+5b=1450
2b=400
b=200
a=150